2012
DOI: 10.3389/fpsyg.2012.00582
|View full text |Cite
|
Sign up to set email alerts
|

Embodied Cognition: Taking the Next Step

Abstract: Recent years have seen a large amount of empirical studies related to “embodied cognition.” While interesting and valuable, there is something dissatisfying with the current state of affairs in this research domain. Hypotheses tend to be underspecified, testing in general terms for embodied versus disembodied processing. The lack of specificity of current hypotheses can easily lead to an erosion of the embodiment concept, and result in a situation in which essentially any effect is taken as positive evidence. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 30 publications
0
48
0
Order By: Relevance
“…Lebois et al (in press) point out that such variability is far more common than often assumed and that even the most entrenched features of concepts are not always activated in an immediate, automatic manner (see also Willems & Casasanto, 2011;Willems & Francken, 2012;Zwaan, 2014). In the same vein, Binder and Desai (2011, p. 531) make the following remarks about their own model of conceptual knowledge: "All levels are not automatically accessed under all conditions.…”
Section: Introductionmentioning
confidence: 98%
“…Lebois et al (in press) point out that such variability is far more common than often assumed and that even the most entrenched features of concepts are not always activated in an immediate, automatic manner (see also Willems & Casasanto, 2011;Willems & Francken, 2012;Zwaan, 2014). In the same vein, Binder and Desai (2011, p. 531) make the following remarks about their own model of conceptual knowledge: "All levels are not automatically accessed under all conditions.…”
Section: Introductionmentioning
confidence: 98%
“…Generally speaking, research findings confirm that parts of the sensory or motor cortex show higher activation when people read vision-or action-related text compared with when they read language that is not related to action or to the senses. The interpretation of these findings is a topic of debate [50][51][52] , but this discussion is beyond the scope of this paper. Here, we focus on how findings from lefthanded participants have helped to increase our understanding of the nature of embodied semantic representations at the neural level.…”
Section: Embodied Cognitionmentioning
confidence: 99%
“…Some previous studies have failed to find sensori-motor cortex involvement during the understanding of action-related language (Postle et al, 2008) or have shown that motor cortex involvement during the comprehension of action verbs depends on task (Desai et al, 2013;Papeo et al, 2009;Sato, 2008). While a lot of discussion has centered around the question whether sensori-motor cortices are important for semantic representations or not, a more fruitful approach seems to be to ask under which circumstances sensori-motor areas play a role in language understanding (Papeo et al, 2009;van Dam et al, 2012;Willems and Casasanto, 2011;Willems and Francken, 2012). The present study adds to this by showing the specific role that emotional context plays in grounding of metaphorical language.…”
Section: Discussionmentioning
confidence: 99%
“…Such findings are often taken as evidence for the embodiment of word meaning (Barsalou, 2008). While that interpretation is debated (Mahon and Caramazza, 2008;Willems and Casasanto, 2011;Willems and Francken, 2012;Wilson and Golonka, 2013), there is evidence that sensori-motor regions of the brain can be involved in coding word meaning.…”
Section: Introductionmentioning
confidence: 99%